Momelotinib in Myelofibrosis Patients With Thrombocytopenia: Post Hoc Analysis From Three Randomized Phase 3 Trials - Kiladjian, Jean-Jacques; Vannucchi, Alessandro M; Gerds, Aaron T; Gupta, Vikas; Verstovsek, Srdan; Egyed, Miklos; Platzbecker, Uwe; Mayer, Jiří; Grosicki, Sebastian; Illés, Árpád; Woźny, Tomasz; Oh, Stephen T; et al. (HemaSphere, 2023)
The oral activin A receptor type I, Janus kinase 1 (JAK1), and JAK2 inhibitor momelotinib demonstrated symptom, spleen, and anemia benefits in intermediate- and high-risk myelofibrosis (MF). Post hoc analyses herein evaluated the efficacy and safety of momelotinib in patients with MF and thrombocytopenia (platelet counts <100 × 109/L) from randomized phase 3 studies: MOMENTUM (momelotinib versus danazol; JAK inhibitor experienced); SIMPLIFY-1 (momelotinib versus ruxolitinib; JAK inhibitor naïve); and SIMPLIFY-2 (momelotinib versus best available therapy; JAK inhibitor experienced); these studies were not statistically powered to assess differences in thrombocytopenic subgroups, and these analyses are descriptive. The treatment effect of momelotinib versus ruxolitinib on week 24 response rates (spleen volume reduction ≥35%/Total Symptom Score reduction ≥50%/transfusion independence) was numerically comparable or better in thrombocytopenic patients versus the overall JAK inhibitor naive population; rates were preserved with momelotinib in thrombocytopenic patients but attenuated with ruxolitinib (momelotinib: 27%/28%/67% overall versus 39%/35%/61% in thrombocytopenic group; ruxolitinib: 29%/42%/49% overall versus 0%/22%/39% in thrombocytopenic group, respectively). In contrast to ruxolitinib, momelotinib maintained high dose intensity throughout the treatment. In the JAK inhibitor experienced population, thrombocytopenic patients had the following: (1) numerically higher symptom and transfusion independence response rates with momelotinib than in control arms; and (2) preserved spleen, symptom, and transfusion independence response rates with momelotinib relative to the overall study populations. The safety profile of momelotinib in thrombocytopenic patients was also consistent with the overall study population. In summary, momelotinib represents a safe and effective treatment option for patients with MF and moderate-to-severe thrombocytopenia.